Intensidad de luz solar en el comportamiento vegetativo en Lactuca sativa L., Loreto - Gonzales Saavedra, Luis Cesar (2023)
Food production under shade systems in the region is an experience since little by little it has been used. The National University of the Amazon, with its Faculty of Agronomy, has been innovating research work like this one entitled USE OF SHADE NETS AND ITS EFFECTS ON THE VEGETATIVE BEHAVIOR OF THE CROP Lactuca sativa L. IN ZUNGAROCOCHA, LORETO - 2022. The present work has a completely randomized design (D.C.A) with three treatments and four repetitions, with the following treatments T1 (100% light), T1 (35% light) and T3 (50% light), the following were obtained: Conclusions: The intensity of light with 35% shade favored the increase in plant height with 23.20 compared to open field with 10.90 cm, for plant width with 36.90 cm compared to open field with 29.80 cm, for plant weight with 216.00 g versus light intensity with 50% shade, of course it is not discrepant with intensity of 35% shade and open field. The cultivation of lettuce in the open field and with light intensity with 35% shade is indifferent in the number of leaves with an average of 16.40 and 15.80 respectively, showing statistical significance with 50% shade.